MtnSEON and social–ecological systems science in complex mountain landscapes. (16th January 2018) - Alessa, Lilian; Kliskey, Andrew; Gosz, James; Griffith, David; Ziegler, Amber
Abstract : The Mountain Social Ecological Observatory Network (MtnSEON) is a US National Science Foundation‐funded Research Coordination Network that focuses on social–ecological systems (SES) science approaches to understanding the vulnerability, resilience, and sustainability of complex mountain landscapes. Papers from members of several MtnSEON working groups are presented in this Special Issue, with topics ranging from applying an SES conceptual approach to social–ecological observatories to dealing with the human aspects of predator–livestock interactions in the American West. All of these articles portray varying degrees of integration of social and ecological sciences and methodologies in order to better address both complex and "wicked" problems inherent to many coupled natural and human systems. The diversity of approaches presented here reflect the different project histories, disciplines being integrated, fields of expertise, and nature of the environmental problems and issues being addressed.